Estimations de la résilience des territoires, sociétés, villes - Samuel Rufat (VertigO)
In recent years, international organizations have increasingly being producing new estimates or measures of resilience to disasters or climate change. On the one hand, UN agencies promote resilience with important financial incentives. On the other hand, they implicitly recognize that it might not possible to measure resilience, or at least to ensure that the different methods actually measure resilience and not another construct – such as poverty – or a proxy – such as vulnerability, etc. This situation is highly paradoxical: how to promote application guides, enjoin local actors to action plans, governments to raise funds, and even follow the progress of projects on the ground of a notion that cannot be safely measured? The field seems overwhelmed by the multitude of theoretical approaches, models and frameworks of resilience emerging endlessly, with virtually no links between them. This proliferation of theoretical frameworks and models seems to fuel a proliferation of methodological approaches to estimating and measuring resilience. However, methodological choices, when they are justified or even mentioned, are much more dependent on access to data than on the theoretical frameworks or the measurement’s objectives. And it seems almost impossible to validate these estimates or to make sure that it is actually resilience they are measuring. This is the most radical criticism that can be addressed to resilience: if it is not possible to measure it, or to validate its measurements, its use must remain confined to discourse analysis.